PERGERAKAN NILAI TUKAR RUPIAH TERHADAP EKSPOR DAN IMPOR INDONESIA - Fitri Ardiya Garini; Weri Weri (Fakultas Ekonomi dan Bisnis UNSYIAH, 2020)
AbstractThis study deals with the Movement of the Rupiah Exchange Rate on Indonesian Exports and Imports with the aim of analyzing the effect of the movement of the Rupiah exchange rate on exports and imports in Indonesia. The variables used are the exchange rate, exports, imports and GDP with the OLS model and annual data for 1990-2017 sourced from the World Bank and the Federal Resereve Economic Data (FRED). The results showed that the exchange rate had a positive and significant relationship to Indonesia's net exports. GDP has a negative and significant effect on net exports. The government is advised to maintain exchange rate stabilization and control the flow of export and import activities in accordance with the movement of the rupiah exchange rate so that Indonesia's economic growth improves.Keywords: Exchange rates, exports, imports, GDP